Sodium manganese ferrite positive electrode material of sodium-ion battery, preparation method and sodium-ion battery

By developing sodium ferromanganate cathode material without expensive elements and using a specific electrolyte to suppress gas production, the problems of high cost, unstable layered structure and gas bloating in the prior art have been solved, and the effects of low-cost and high cycle stability have been achieved.

CN119560549AInactive Publication Date: 2025-03-04JIANGSU HAONA NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598537.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide positive electrode materials have high costs, unstable layered structure and gas bloating problems, which affect the cycle stability and safety of the battery.

Method used

A low-cost sodium ion battery sodium ferromanganate positive electrode material without Ni, Co, Cu and other elements was developed to improve the stability of its layered structure through doping of specific metal elements, and two specific electrolytes were used to inhibit gas production.

Benefits of technology

The low cost, high cycle stability and suppression of bloating of sodium ferromanganate cathode material are achieved, which significantly reduces material costs and improves the operating stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560549A_ABST
    Figure CN119560549A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium manganese ferrite positive electrode material of a sodium-ion battery and a preparation method of the sodium manganese ferrite positive electrode material, and belongs to the technical field of sodium-ion batteries. The chemical composition of the sodium manganese ferrite positive electrode material of the sodium ion battery is NaaMnbFecXdO2-beta, hereinafter referred to as NMFX, 0.6 < = a < = 0.9, 0.45 < = b < = 0.85, 0.25 < = c < = 0.55, 0 < = d < = 0.15, and 0 < = beta < = 1. Compared with a positive electrode material containing elements such as Ni, Cu and Co, the prepared sodium manganese ferrite positive electrode material of the sodium-ion battery is extremely low in cost, the P2-phase sodium manganese ferrite positive electrode material is good in high-voltage performance, and the sodium manganese ferrite positive electrode material of the sodium-ion battery prepared after metal lithium ion doping modification is excellent in cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery sodium manganese ferrite positive electrode material, a preparation method and a sodium ion battery. Background Art

[0002] In recent years, the development and application of sodium-ion batteries have received more and more attention, especially sodium-ion battery layered oxides, because they are very compatible with the lithium-ion battery ternary positive electrode production line and have the potential to be the first to be mass-produced. However, layered oxides also have many problems to be solved: 1) With the decline in the price of upstream lithium salts, sodium-ion battery layered oxide positive electrode materials containing expensive metal elements such as Ni and Co no longer have cost advantages; 2) Due to the existence of the Chiang-Taylor effect, manganese-based materials have a high Mn content during the charge and discharge process. 3+ / Mn 4+ The transition between them will cause the dissolution of manganese, resulting in the instability of the layered structure of the positive electrode material; 3) In general nickel-iron-manganese or nickel-copper-iron-manganese layered oxygen materials, the presence of iron will affect the deintercalation of sodium ions, and will also affect the stability of the layered structure, thereby causing the battery cycle to deteriorate.

[0003] At the same time, as an emerging energy storage technology, sodium-ion batteries have the advantages of abundant resources and low cost, but there are also some challenges in practical applications, among which the gas expansion problem is an important research direction. The gas expansion problem may cause the internal pressure of the battery to increase, affecting the performance and safety of the battery. The gas expansion phenomenon usually stems from several key factors: first, oxygen precipitation is prone to occur at the positive electrode when it is fully charged; second, the solid electrolyte interface (SEI) layer of the negative electrode fails to completely cover the micropores of the amorphous carbon, resulting in the generation of gas when the electrolyte contacts sodium. This gas generation process will accelerate the decline of battery performance, thereby affecting its long-term operational stability. Summary of the invention

[0004] The first purpose of the present invention is to provide: a low-cost sodium ion battery sodium manganese ferrite positive electrode material that does not contain elements such as Ni, Co, and Cu, the purpose of which is to improve the stability of its layered structure by doping with specific metal elements, thereby improving the cycle stability of the positive electrode material.

[0005] A sodium ion battery sodium manganese ferrite positive electrode material, the chemical formula of the positive electrode material is Na a Mn b Fe c X d O 2-β, wherein 0.6≤a≤0.9, 0.45≤b≤0.85, 0.25≤c≤0.55, 0≤d≤0.15, 0≤β≤1, and X is at least one element selected from Ca, Zn, Li, Mg, Zr, Ti, B, Nb, W, V, Si, Sr, Mo, Y and Al.

[0006] The sodium ion battery sodium manganese ferrite positive electrode material meets at least one of the following conditions:

[0007] (1) 0.75≤a≤0.85;

[0008] (2) 0.45≤b≤0.65;

[0009] (3) 0.25≤c≤0.45;

[0010] (4)0≤d≤0.13.

[0011] The second object of the present invention is to provide: a method for preparing sodium ferromanganate, a positive electrode precursor of a sodium ion battery, comprising the following steps:

[0012] Step 1, mixing once, weighing a manganese source and an iron source according to a metal molar ratio of α:(1-α), mixing by a planetary ball mill to obtain a manganese-iron mixture, wherein 0.45≤α≤0.85;

[0013] Step 2: sintering once to subject the mixed manganese-iron mixture to a high-temperature solid-phase reaction to obtain a sodium ferromanganate positive electrode material precursor.

[0014] In the step 1, the manganese source is selected from at least one of manganese oxide, manganese carbonate and manganese hydroxide; the iron source is selected from at least one of ferric oxide and ferrous hydroxide; the sodium source is selected from at least one of sodium carbonate and sodium bicarbonate; the main disc speed of the planetary ball mill in step 1 is 50-200 rpm / min, and the mixing time is 0.5-2h;

[0015] In the step 2, the high temperature solid phase reaction temperature is 550-950° C., the sintering time is 5-20 hours, and the sintering atmosphere is air atmosphere.

[0016] The third object of the present invention is to provide: a method for preparing a sodium ion battery sodium manganese ferrite positive electrode material, comprising the following steps:

[0017] Step 1: primary crushing: crushing the precursor material obtained by sintering with an experimental airflow crusher;

[0018] Step 2, secondary mixing, weighing the crushed precursor material, sodium source and additive according to the metal molar ratio of a:b:c:d, and mixing them using a test type high-efficiency mixer;

[0019] Step 3: secondary sintering: placing the mixed materials in a muffle furnace for sintering in an air atmosphere to obtain a secondary sintered product;

[0020] Step 4: secondary crushing: crushing the NMFX material after secondary sintering with a test airflow crusher to obtain NMFX material;

[0021] Step 5: Screen and demagnetize the NMFX material after secondary crushing to obtain sodium manganese ferrite positive electrode material NMFX.

[0022] In the step 1, the grinding air pressure of the air flow mill is 0.4-0.8 MPa, the classification frequency is 25-45 Hz, the induced draft frequency is 15-35 Hz, and the particle size of the material after grinding is D10=2.5±0.5 μm, D50=7.0±0.5 μm, and D90=12.5±0.5 μm;

[0023] In the step 2, the low speed of the mixer is 200-500 rpm / min, the mixing time is 2-10 min, the high speed is 700-1000 rpm / min, the mixing time is 10-50 min; the unloading speed is 200-500 rpm / min, and the unloading time is 30-60 s;

[0024] In the step 3, the secondary sintering time is 10-25h, and the sintering temperature is 800-1000°C;

[0025] In the step 4, the grinding air pressure of the air flow mill is 0.4-0.8 MPa, the classification frequency is 25-45 Hz, the induced draft frequency is 15-35 Hz, and the particle size of the material after grinding is D10=2.5±0.5 μm, D50=5.5±0.5 μm, and D90=10±0.5 μm.

[0026] The fourth object of the present invention is to provide: a sodium ion battery positive electrode precursor sodium manganese ferrite, which is obtained by the preparation method of the second object of the present invention; the sodium ion battery positive electrode precursor sodium manganese ferrite, the tap density of the precursor satisfies TD≥2.3g / cm 3 , the particle size distribution satisfies Span (D90-D10 / D50) ≥ 1.3, and the specific surface area satisfies BET ≥ 0.9 m2 / g.

[0027] The fifth object of the present invention is to provide: a lithium-doped sodium ion battery positive electrode precursor sodium manganese ferrite, the chemical formula of the precursor is Na a Mn b Fe c Li dO2, wherein 0.75≤a≤0.85, 0.45≤b≤0.5, 0.4≤c≤0.45, 0.05≤d≤0.13; the lithium source of the precursor is selected from at least one of lithium carbonate and lithium hydroxide monohydrate.

[0028] The sixth object of the present invention is to provide: a sodium ion battery capable of suppressing gas production, the sodium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator, and a first electrolyte and a second electrolyte;

[0029] The surfaces of the positive electrode sheet and the negative electrode sheet contain a carbon-based conductive agent, and the carbon-based conductive agent is selected from one or a mixture of hard carbon, carbon black, PVDF, PTFE, and carbon fiber;

[0030] The first electrolyte includes: a cross-linking monomer, a diluent, a solute and an initiator, wherein the cross-linking monomer refers to a monomer having at least one functional group selected from the group consisting of a carboxyl group, a hydroxyl group, a ketone group, an ether group, an amino group, and a sulfonic group.

[0031] The first electrolyte of the sodium ion battery also includes the following features:

[0032] The weight ratio of the diluent is (60-90):(10-30), and the first electrolyte further contains 0.1-5 mol / L of solute and 0.1-3 wt% of initiator by mass percentage, the diluent is a carbonate diluent, the solute is NaPF6, and the initiator is AIBN;

[0033] The cross-linking monomer is selected from the following group or a combination of several groups:

[0034] Group 1: vinylene carbonate (VC) and acrylonitrile (AN); and the weight ratio range is 30-60:20-40;

[0035] Group 2: polyethylene glycol diacrylate (PEGDA) and ethoxylated trimethylolpropane triacrylate (ETPTA); and the weight ratio range is 30-50:30-50;

[0036] Group 3: 1,3-dioxolane (DOL), fluoroethylene carbonate (FEC), hexamethylene diisocyanate (HDI); and the weight ratio range is 10-30:10-25:10-25.

[0037] The seventh object of the present invention is to provide a method for preparing a sodium ion battery with suppressed gas production, comprising the following steps:

[0038] Step 1, assembling the positive electrode sheet, the negative electrode sheet, and the separator into a battery cell;

[0039] Step 2, injecting a first electrolyte into the battery cell;

[0040] Step 3, heating treatment;

[0041] Step 4: inject a second electrolyte into the battery cell.

[0042] In step 2, the dew point temperature of the air is maintained below -45°C during the injection process.

[0043] In step 3, the temperature treatment refers to 60-85° C. for 1-10 hours.

[0044] The eighth object of the present invention is to provide the application of the above-mentioned sodium ion battery that can inhibit gas production in the preparation.

[0045] Beneficial Effects

[0046] A sodium ferromanganate positive electrode material for a sodium ion battery is synthesized which does not contain expensive elements such as Ni, Co, and Cu. At present, the price per ton of sodium ferromanganate or sodium ferromanganate positive electrode materials synthesized by a hydroxide precursor process route in the market is between 5w and 7w. The price per ton of the sodium ferromanganate positive electrode material for a sodium ion battery proposed by the invention is between 1w and 3w, which greatly reduces the material cost. The P2 phase sodium ferromanganate positive electrode material has good high voltage performance. The layered structure of the sodium ferromanganate positive electrode material is improved by doping with metal elements. During the charge and discharge process, the influence of the Jan-Taylor effect on the manganese-based material is effectively suppressed, the dissolution problem of manganese ions is improved, the layered structure is more stable, which is conducive to the release and embedding of sodium ions during the charge and discharge process, and the cycle stability of the material is relatively excellent.

[0047] During the battery assembly process, two specific electrolytes were used. The first electrolyte can bond with amorphous carbon on the electrode surface through hydrogen bonds and has the ability to self-crosslink, thereby forming a protective layer that effectively prevents the electrolyte from directly contacting the sodium in the amorphous carbon, reducing gas generation while ensuring the free migration of sodium ions. Combined with the use of the second electrolyte, this combination not only maintains the stability of the electrode structure, but also significantly enhances the operational stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 : Scanning electron microscope (SEM) image of the sodium ion battery sodium manganese ferrite positive electrode material precursor MF in Example 2

[0049] Figure 2 : Scanning electron microscope (SEM) image of sodium manganese ferrite positive electrode material NMF for sodium ion battery in Example 1

[0050] Figure 3 :In Example 1, sodium ferromanganese oxide positive electrode material Na for sodium ion battery 0.7 Mn 99 / 204 Fe 81 / 204 Li24 / 204 XRD pattern of O2

[0051] Figure 4 : In Example 2, sodium ferromanganese oxide positive electrode material Na for sodium ion battery 0.75 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 XRD pattern of O2

[0052] Figure 5 : In Example 3, sodium ferromanganese oxide positive electrode material Na for sodium ion battery 0.8 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 XRD pattern of O2

[0053] Figure 6 : In Example 4, sodium ferromanganese oxide positive electrode material Na for sodium ion battery 0.85 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 XRD pattern of O2

[0054] Figure 7 :Comparative Example 1 Sodium ion battery sodium manganese ferrite positive electrode material Na 0.75 Mn 0.55 Fe 0.45 XRD pattern of O2

[0055] Figure 8 : Na in Example 2 0.75 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 O2 and Na in Comparative Example 1 0.75 Mn 0.55 Fe 0.45 First cycle charge and discharge curves of two cathode materials of O2

[0056] Fig. 9 : Na in Example 2 0.75 Mn 0.6 Fe 0.3 Li 0.1 O2 and Na in Comparative Example 1 0.75 Mn 0.55 Fe 0.45 Cyclic performance curves of two cathode materials for O2 DETAILED DESCRIPTION

[0057] The present invention is further described in detail below with reference to specific examples and comparative examples. The present invention can be implemented in many different forms and is not limited to the embodiments described herein.

[0058] Example 1

[0059] Na 0.7 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The preparation method of the O2 sodium ion battery positive electrode material precursor and the sodium ion battery positive electrode material is as follows:

[0060] Step 1: Mixing once, weighing a manganese source and an iron source according to a metal molar ratio of 0.55:0.45, and mixing them in a planetary ball mill to obtain a manganese-iron mixture. The selected manganese source is manganese oxide, the selected iron source is iron oxide, the mixing time of the planetary ball mill is 1.5 hours, and the main disc speed of the ball mill is 150 rpm / min;

[0061] Step 2: sintering once, placing the mixed manganese iron mixture in a muffle furnace, sintering for 15 hours under air atmosphere, and the sintering temperature is 800° C. to obtain sodium manganese ferrite positive electrode material precursor MF;

[0062] Step 3: Primary crushing: crush the sintered MF material with a pilot jet mill to obtain crushed MF material. The jet mill has a grinding pressure of 0.6 MPa, a classification frequency of 30 Hz, and an induced draft frequency of 25 Hz. The particle size of the crushed material is D 10 =2.5±0.5μm, D 50 =7.0±0.5μm, D 90 =12.5±0.5μm;

[0063] Step 4: Secondary mixing: weigh the crushed MF material and sodium source according to the sodium ratio = 0.7, then add the lithium source according to the molar ratio, and use a test-type high-efficiency mixer to mix. The low speed of the high-efficiency mixer is 200rpm / min, the mixing time is 5min, the high speed is 800rpm / min, the mixing time is 30min, the unloading speed is 200rpm / min, and the unloading time is 60s. The selected sodium source is battery-grade sodium carbonate, and the selected lithium source is battery-grade lithium carbonate.

[0064] Step 5: Secondary sintering: Place the mixed materials in a muffle furnace for sintering under air atmosphere for 20 hours at a secondary sintering temperature of 950°C to obtain sodium manganese ferrite positive electrode material Na 0.7 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 O2;

[0065] Step 6: Secondary crushing, the Na 0.7 Mn 99 / 204 Fe 81 / 204 Li 24 / 204The O2 material was crushed by an experimental airflow mill to obtain the final positive electrode material. The airflow mill grinding pressure was 0.6MPa, the classification frequency was 35Hz, the induced draft frequency was 25Hz, and the particle size of the crushed material was D 10 =2.5±0.5μm, D 50 =5.5±0.5μm, D 90 =10±0.5μm;

[0066] Step 7: Screen and demagnetize the secondary crushed positive electrode material to obtain the final product.

[0067] Example 2

[0068] The difference from Example 1 is that the sodium ratio of the positive electrode material in Example 2 is 0.75.

[0069] Na 0.75 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The preparation method of the O2 sodium ion battery positive electrode material precursor and the sodium ion battery positive electrode material is as follows:

[0070] Step 1: Mixing once, weighing a manganese source and an iron source according to a metal molar ratio of 0.55:0.45, and mixing them in a planetary ball mill to obtain a manganese-iron mixture. The selected manganese source is manganese oxide, the selected iron source is iron oxide, the mixing time of the planetary ball mill is 1.5 hours, and the main disc speed of the ball mill is 150 rpm / min;

[0071] Step 2: sintering once, placing the mixed manganese iron mixture in a muffle furnace, sintering for 15 hours under air atmosphere, and the sintering temperature is 800° C. to obtain sodium manganese ferrite positive electrode material precursor MF;

[0072] Step 3: Primary crushing: crush the sintered MF material with a pilot jet mill to obtain crushed MF material. The jet mill has a grinding pressure of 0.6 MPa, a classification frequency of 30 Hz, and an induced draft frequency of 25 Hz. The particle size of the crushed material is D 10 =2.5±0.5μm, D 50 =7.0±0.5μm, D 90 =12.5±0.5μm;

[0073] Step 4: Secondary mixing: weigh the crushed MF material and sodium source according to the sodium ratio = 0.75, then add the lithium source according to the molar ratio, and use a test-type high-efficiency mixer to mix. The low speed of the high-efficiency mixer is 200rpm / min, the mixing time is 5min, the high speed is 800rpm / min, the mixing time is 30min, the unloading speed is 200rpm / min, and the unloading time is 60s. The selected sodium source is battery-grade sodium carbonate, and the selected lithium source is battery-grade lithium carbonate.

[0074] Step 5: Secondary sintering: Place the mixed materials in a muffle furnace for sintering under air atmosphere for 20 hours at a secondary sintering temperature of 950°C to obtain sodium manganese ferrite positive electrode material Na 0.75 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 O2;

[0075] Step 6: Secondary crushing, the Na 0.75 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The O2 material was crushed by an experimental airflow mill to obtain the final positive electrode material. The airflow mill grinding pressure was 0.6MPa, the classification frequency was 35Hz, the induced draft frequency was 25Hz, and the particle size of the crushed material was D 10 =2.5±0.5μm, D 50 =5.5±0.5μm, D 90 =10±0.5μm;

[0076] Step 7: Screen and demagnetize the secondary crushed positive electrode material to obtain the final product.

[0077] Example 3

[0078] The difference from Example 1 is that the sodium ratio of the positive electrode material in Example 3 is 0.8.

[0079] Na 0.8 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The preparation method of the O2 sodium ion battery positive electrode material precursor and the sodium ion battery positive electrode material is as follows:

[0080] Step 1: Mixing once, weighing a manganese source and an iron source according to a metal molar ratio of 0.55:0.45, and mixing them in a planetary ball mill to obtain a manganese-iron mixture. The selected manganese source is manganese oxide, the selected iron source is iron oxide, the mixing time of the planetary ball mill is 1.5 hours, and the main disc speed of the ball mill is 150 rpm / min;

[0081] Step 2: sintering once, placing the mixed manganese iron mixture in a muffle furnace, sintering for 15 hours under air atmosphere, and the sintering temperature is 800° C. to obtain sodium manganese ferrite positive electrode material precursor MF;

[0082] Step 3: Primary crushing: crush the sintered MF material with a pilot jet mill to obtain crushed MF material. The jet mill has a grinding pressure of 0.6 MPa, a classification frequency of 30 Hz, and an induced draft frequency of 25 Hz. The particle size of the crushed material is D 10=2.5±0.5μm, D 50 =7.0±0.5μm, D 90 =12.5±0.5μm;

[0083] Step 4: Secondary mixing: weigh the crushed MF material and sodium source according to the sodium ratio = 0.8, then add the lithium source according to the molar ratio, and mix them using a test-type high-efficiency mixer. The low speed of the high-efficiency mixer is 200 rpm / min, the mixing time is 5 min, the high speed is 800 rpm / min, the mixing time is 30 min, the unloading speed is 200 rpm / min, and the unloading time is 60 s. The selected sodium source is battery-grade sodium carbonate, and the selected lithium source is battery-grade lithium carbonate.

[0084] Step 5: Secondary sintering: Place the mixed materials in a muffle furnace for sintering under air atmosphere for 20 hours at a secondary sintering temperature of 950°C to obtain sodium manganese ferrite positive electrode material Na 0.8 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 O2;

[0085] Step 6: Secondary crushing, the Na 0.8 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The O2 material was crushed by an experimental airflow mill to obtain the final positive electrode material. The airflow mill grinding pressure was 0.6MPa, the classification frequency was 35Hz, the induced draft frequency was 25Hz, and the particle size of the crushed material was D 10 =2.5±0.5μm, D 50 =5.5±0.5μm, D 90 =10±0.5μm;

[0086] Step 7: Screen and demagnetize the secondary crushed positive electrode material to obtain the final product.

[0087] Example 4

[0088] The difference from Example 1 is that the sodium ratio of the positive electrode material in Example 4 is 0.85.

[0089] Na 0.8 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The preparation method of the O2 sodium ion battery positive electrode material precursor and the sodium ion battery positive electrode material is as follows:

[0090] Step 1: Mixing once, weighing a manganese source and an iron source according to a metal molar ratio of 0.55:0.45, and mixing them in a planetary ball mill to obtain a manganese-iron mixture. The selected manganese source is manganese oxide, the selected iron source is iron oxide, the mixing time of the planetary ball mill is 1.5 hours, and the main disc speed of the ball mill is 150 rpm / min;

[0091] Step 2: sintering once, placing the mixed manganese iron mixture in a muffle furnace, sintering for 15 hours under air atmosphere, and the sintering temperature is 800° C. to obtain sodium manganese ferrite positive electrode material precursor MF;

[0092] Step 3: Primary crushing: crush the sintered MF material with a pilot jet mill to obtain crushed MF material. The jet mill has a grinding pressure of 0.6 MPa, a classification frequency of 30 Hz, and an induced draft frequency of 25 Hz. The particle size of the crushed material is D 10 =2.5±0.5μm, D 50 =7.0±0.5μm, D 90 =12.5±0.5μm;

[0093] Step 4: Secondary mixing: weigh the crushed MF material and sodium source according to the sodium ratio = 0.85, then add the lithium source according to the molar ratio, and mix them using a test-type high-efficiency mixer. The low speed of the high-efficiency mixer is 200 rpm / min, the mixing time is 5 min, the high speed is 800 rpm / min, the mixing time is 30 min, the unloading speed is 200 rpm / min, and the unloading time is 60 s. The selected sodium source is battery-grade sodium carbonate, and the selected lithium source is battery-grade lithium carbonate.

[0094] Step 5: Secondary sintering: Place the mixed materials in a muffle furnace for sintering under air atmosphere for 20 hours at a secondary sintering temperature of 950°C to obtain sodium manganese ferrite positive electrode material Na 0.85 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 O2;

[0095] Step 6: Secondary crushing, the Na 0.85 Mn 99 / 204 Fe 81 / 204 Li 24 / 204 The O2 material was crushed by an experimental airflow mill to obtain the final positive electrode material. The airflow mill grinding pressure was 0.6MPa, the classification frequency was 35Hz, the induced draft frequency was 25Hz, and the particle size of the crushed material was D 10 =2.5±0.5μm, D 50 =5.5±0.5μm, D 90 =10±0.5μm;

[0096] Step 7: Screen and demagnetize the secondary crushed positive electrode material to obtain the final product.

[0097] Comparative Example 1

[0098] The difference from Example 2 is that the positive electrode material of Comparative Example 1 is not doped with Li, and the sodium ratio of both Example 2 and Comparative Example 1 is 0.75.

[0099] Na 0.75 Mn 55 Fe 45 The preparation method of the O2 sodium ion battery positive electrode material precursor and the sodium ion battery positive electrode material is as follows:

[0100] Step 1: Mixing once, weighing a manganese source and an iron source according to a metal molar ratio of 0.55:0.45, and mixing them in a planetary ball mill to obtain a manganese-iron mixture. The selected manganese source is manganese oxide, the selected iron source is iron oxide, the mixing time of the planetary ball mill is 1.5 hours, and the main disc speed of the ball mill is 150 rpm / min;

[0101] Step 2: sintering once, placing the mixed manganese iron mixture in a muffle furnace, sintering for 15 hours under air atmosphere, and the sintering temperature is 800° C. to obtain sodium manganese ferrite positive electrode material precursor MF;

[0102] Step 3: Primary crushing: crush the sintered MF material with a pilot jet mill to obtain crushed MF material. The jet mill has a grinding pressure of 0.6 MPa, a classification frequency of 30 Hz, and an induced draft frequency of 25 Hz. The particle size of the crushed material is D 10 =2.5±0.5μm, D 50 =7.0±0.5μm, D 90 =12.5±0.5μm;

[0103] Step 4: Secondary mixing: weigh the crushed MF material and sodium source according to the sodium ratio = 0.75, and mix them in a test-type high-efficiency mixer. The low speed of the high-efficiency mixer is 200 rpm / min, the mixing time is 5 min, the high speed is 800 rpm / min, the mixing time is 30 min, the unloading speed is 200 rpm / min, and the unloading time is 60 s. The selected sodium source is battery-grade sodium carbonate.

[0104] Step 5: Secondary sintering: Place the mixed materials in a muffle furnace for sintering under air atmosphere for 20 hours at a secondary sintering temperature of 950°C to obtain sodium manganese ferrite positive electrode material Na 0.75 Mn 55 Fe 45 O2;

[0105] Step 6: Secondary crushing, the Na 0.75 Mn55 Fe 45 The O2 material was crushed by an experimental airflow mill to obtain the final positive electrode material. The airflow mill grinding pressure was 0.6MPa, the classification frequency was 35Hz, the induced draft frequency was 25Hz, and the particle size of the crushed material was D 10 =2.5±0.5μm, D 50 =5.5±0.5μm, D 90 =10±0.5μm;

[0106] Step 7: Screen and demagnetize the secondary crushed positive electrode material to obtain the final product.

[0107] Figure 1 and Figure 2 The scanning electron microscope images in the figure are the morphology of the sodium ion battery sodium manganese ferrite positive electrode material precursor MF and the morphology of the sodium ion battery sodium manganese ferrite positive electrode material NMF. It can be seen from the figure that both materials are single crystal materials, which shows that the whole process route is successful and the sodium ion battery sodium manganese ferrite positive electrode material and its precursor have been synthesized.

[0108] By comparing the XRD patterns of Example 2 and Comparative Example 1, it can be found that the modified NMF is still a P2 phase material. Figures 3 to 6 The XRD spectrum of sodium manganese ferrite positive electrode materials of lithium-doped sodium ion batteries with different sodium ratios in the results show that with the increase of Na ratio, the second highest characteristic peak of the P2 phase of the (012) crystal plane between 39 degrees and 40 degrees gradually decreases, which means that the material gradually transforms to the O3 phase material with the increase of sodium ratio, and there are no other impurity peaks near the first highest characteristic peak of the P2 phase of the (002) crystal plane between 16 degrees and 17 degrees. The (002) crystal plane peak of the sodium manganese ferrite positive electrode material after lithium doping slightly shifts to a lower angle, indicating that the interlayer spacing of the layered oxygen structure becomes larger, which is conducive to the release and embedding of sodium ions in the layered structure during charging and discharging. It is proved that the layered oxygen structure of the sodium manganese ferrite positive electrode material after lithium doping is more stable, which weakens the influence of the Jiang-Taylor effect to a certain extent and solves the problem of manganese dissolution in manganese-based materials. By means of doping, the interlayer spacing of the structure is increased, which inhibits the iron / sodium mixed arrangement to a certain extent, reduces the influence of iron ions on the release and embedding of sodium ions, stabilizes the layered structure of the material, and improves the cycle stability of the battery.

[0109] In the electrochemical performance test, the battery was assembled by the following method: the positive electrode material, acetylene black, and PVDF were mixed uniformly in NMP solvent according to a weight ratio of 8:1:1, uniformly coated on the aluminum foil current collector, and vacuum dried at 120°C to form a positive electrode sheet. Metal sodium sheet and glass fiber membrane were used as the counter electrode and diaphragm, respectively, and 1.0M NaPF6 EC+DEC (volume ratio 1:1) was used as the electrolyte. CR2032 button cells were assembled in an argon protection glove box. The electrical performance test results are shown in Table 1.

[0110] Table 1 Electrical performance test results

[0111]

[0112] It can be seen from Table 1 that when the nominal capacity is 100 mAh g -1 , in the charge and discharge range of 2.2V-4.2V, comparing Example 2 with Comparative Example 1, the sodium manganese ferrite positive electrode material after lithium doping has greatly improved both the discharge capacity and the cycle performance, proving that the problem of poor cycle performance of manganese-based materials can be solved by lithium doping, which is consistent with the XRD diffraction results. The layered structure of the material modified by lithium doping is stabilized, which inhibits the dissolution of manganese in the manganese-based material during the charge and discharge process. At the same time, the increase in the interlayer spacing of the layered structure also makes it easier for sodium ions to be removed and embedded during the charge and discharge process, effectively alleviating the iron / sodium mixed row, and greatly enhancing the electrochemical performance of the material. In the absence of elements such as Ni and Co, such a stable and low-cost layered oxide material for sodium ion batteries is obtained. There is no doubt that the present invention has achieved great success.

[0113] The present invention also discloses a sodium ion battery that can inhibit gas production. The preparation process of the battery includes: after the battery is packaged and baked, it is fixed with a clamp, and the first type of electrolyte is injected, sealed and left for a period of time. After that, it is placed in an oven and heated under vacuum. Then the second type of electrolyte is injected, and it continues to be left aside, followed by formation and volume separation processes, and finally the sodium ion battery of the present invention is made. The core of the technology lies in that the surface of the negative electrode hard carbon is coated with an organic film, which is formed by hydrogen bonding of functional groups (such as carboxyl, hydroxyl, ketone, etc.) carried by the solvent in the first type of electrolyte and similar functional groups (such as carboxyl, lactone, phenolic hydroxyl and carbonyl, etc.) introduced into the hard carbon surface during the preparation process. This combination not only forms a network structure, but also the first type of electrolyte can be polymerized into a cross-linked body, which effectively prevents the electrolyte from directly contacting the sodium in the hard carbon to produce gas, while allowing the free transmission of sodium ions. In addition, this design can also reduce the direct contact area between the positive electrode active material and the electrolyte, and reduce the side reactions between the two.

[0114] During the battery assembly stage, the conventional sodium-ion battery production process can be followed, including stirring, coating, rolling, slitting, laminating, welding the pole ears, punching the shell and packaging, and then baking. For cylindrical cells, they are wound and shelled after slitting, and the connecting pieces and caps are welded, and then baked again. Square aluminum shell cells can be wound or laminated, and then the Mylar film, connecting pieces, cover plates, bottom plates, shells are welded, and finally laser welding is performed before baking.

[0115] The electrolyte injection process is required to be carried out in a low humidity environment to ensure that the electrolyte is effectively distributed in the battery cell without introducing water vapor to avoid premature cross-linking and curing. After the first type of electrolyte is injected, it may be necessary to leave it at high temperature for a period of time to promote the cross-linking of the components in the electrolyte with the functional groups on the electrode surface through hydrogen bonds, and to self-cross-link to form a cross-linking layer that inhibits gas production. After the second type of electrolyte is injected, it will mainly play the role of ion transmission.

[0116] The first type of electrolyte contains at least one functional group such as carboxyl, hydroxyl, ketone, ether, amino, and sulfonic groups, which can be combined with the functional groups on the surface of amorphous carbon, and its solvent contains at least one monomer combination that can be polymerized. Through the hydrogen bonds with similar functional groups on the amorphous carbon in a network, or polymerized into a cross-linked body, it can not only prevent the electrolyte from directly contacting the sodium in the amorphous carbon to produce gas, but also allow sodium ions to pass freely. The solute of the first type of electrolyte is one or more of the sodium salts of NaClO4, NaPF6, NaTFSi, NaFSi, NaOTF, NaBF4, NaBOB, and NaDFOB, and may also contain a small amount of initiator to promote cross-linking.

[0117] The second type of electrolyte contains at least one specific component, such as ionic liquid, polyfluorocarbonate, polyfluoroether, etc., and its solute is also one or more of NaClO4, NaPF6, NaTFSi, NaFSi, NaOTF, NaBF4, NaBOB, NaDFOB. It may also contain no solute and may also contain a small amount of carbonate diluent.

[0118] The sodium ion battery of the present invention adopts layered oxides and polyanion sodium compounds as positive electrode materials, and uses amorphous carbon materials such as hard carbon and soft carbon as negative electrode materials.

[0119] Example 5 5Ah sodium ion soft-pack battery cell prepared by the present invention

[0120] Step 1: Prepare the positive electrode sheet. According to the weight ratio of 96:1.5:2.0:0.5, put the ternary sodium positive electrode material, conductive carbon black, PVDF and carbon fiber into a stirring kettle and mix them. After stirring for 30 minutes, add NMP until the solid content reaches 60%, and continue to stir at high speed for 3 hours. The obtained slurry is 190mg / m 2The surface density is evenly coated on a 12um thick aluminum foil, and then rolled, slit and die-cut to form the positive electrode sheet.

[0121] Step 2: Prepare the negative electrode sheet. Weigh 18 kg of hard carbon material, conductive carbon black, PTFE and carbon fiber in a ratio of 96.5:1.0:2:0.5, and prepare it using the same process as the positive electrode sheet.

[0122] Step 3: Assemble the battery cell. Alternately stack 35 positive electrode sheets and 36 negative electrode sheets with PP separators to form a battery cell. Then weld the tabs, encapsulate the aluminum-plastic film, and place the battery in a vacuum environment until the pressure drops to 13 Pa, and then bake it within 48 hours.

[0123] Step 4: Inject the first type of electrolyte into the battery cell. The first type of electrolyte is a mixture of vinylene carbonate (VC), acrylonitrile (AN), ethylene carbonate (EC), and diethyl carbonate (DEC) in a ratio of 49:31:10:10, containing 0.5 mol / L NaPF6 and 0.5% mass ratio of initiator AIBN. After injecting the electrolyte at 45°C, the battery cell is vacuum sealed and left for 48 hours.

[0124] Step 5: Heating treatment: Use a restraint fixture to fix the battery cell and heat it at 75°C for 3 hours.

[0125] Step six, inject the second type of electrolyte into the battery cell. After heating, cut the battery cell mouth and inject the second type of electrolyte, which is a mixture of FEC, 2-fluoro-1,3-dimethylimidazolium chloride hexafluorophosphate, and EC in a weight ratio of 3:6:1, and add 0.5 mol / L NaPF6. Then evacuate and seal the battery cell, and leave it at 45°C for 48 hours to complete the battery formation process. After formation, leave it at room temperature for 24 hours, perform the second sealing and capacity separation process, and finally obtain a sodium ion battery that can inhibit gas production.

[0126] Example 6

[0127] The main differences from Example 5 are the capacity of the battery cell, the amount of positive and negative electrode materials, the surface density of the positive electrode coating, and the solvent composition of the electrolyte. These differences reflect the specific requirements of different battery cell designs for materials and process parameters.

[0128] Step 1: Prepare the positive electrode sheet. According to the weight ratio of 96:1.5:2.0:0.5, put the ternary sodium positive electrode material, conductive carbon black, PVDF and carbon fiber into a stirring kettle and mix them. After stirring for 30 minutes, add NMP until the solid content reaches 60%, and continue to stir at high speed for 3 hours. The obtained slurry is 180mg / m 2 The surface density is evenly coated on a 12um thick aluminum foil, and then rolled, slit and die-cut to form the positive electrode sheet.

[0129] Step 2: Prepare the negative electrode sheet: Weigh 36 kg of hard carbon material, conductive carbon black, PTFE and carbon fiber in a ratio of 96.5:1.0:2:0.5, and prepare the negative electrode sheet using the same process as the positive electrode sheet.

[0130] Step 3: Assemble the battery cell. Alternately stack 40 positive electrode sheets and 41 negative electrode sheets with PP separators to form a battery cell. Then weld the tabs, encapsulate the aluminum-plastic film, and place the battery in a vacuum environment until the pressure drops to 13 Pa, and then bake it within 48 hours.

[0131] Step 4: Inject the first type of electrolyte into the battery cell. The first type of electrolyte is a mixture of PEGDA, ETPTA, EC, and DEC in a ratio of 40:40:10:10, containing 0.5 mol / L NaPF6 and 0.5% by mass of initiator AIBN. After injecting the electrolyte at 45°C, the battery cell is vacuum sealed and left for 48 hours.

[0132] Step 5: Heating treatment: Use a restraint fixture to fix the battery cell and heat it at 75°C for 3 hours.

[0133] Step six, inject the second type of electrolyte into the battery cell. After heating, cut the battery cell opening and inject the second type of electrolyte, which is a mixture of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1-hexyl-3-methylimidazolium tetrafluoroborate, and EC in a weight ratio of 3:6:1, and add 0.5 mol / L of NaPF6. Then evacuate and seal the battery cell, and leave it at 45°C for 48 hours to complete the battery formation process. After formation, leave it at room temperature for 24 hours, perform secondary sealing, laser weld the aluminum plate of the injection hole, and divide the volume, and finally obtain a sodium ion battery that can inhibit gas production.

[0134] Example 7 12Ah sodium ion soft-pack battery cell prepared by the present invention

[0135] In Example 5 and Example 7, we manufactured 5Ah sodium ion soft-pack batteries and 12Ah cylindrical sodium ion batteries, respectively, using the same process flow, but with differences in battery design, electrolyte formulation and some process parameters.

[0136] Step 1: Prepare the positive electrode sheet. According to the weight ratio of 96:1.5:2.0:0.5, put the polyanion sodium positive electrode material, conductive carbon black, PVDF, and carbon fiber into a stirring kettle and mix them. After stirring for 30 minutes, add NMP until the solid content reaches 60%, and continue to stir at high speed for 3 hours. The obtained slurry is 190 mg / m 2 The surface density is evenly coated on a 12um thick aluminum foil, and then rolled, slit and die-cut to form the positive electrode sheet.

[0137] Step 2: Prepare the negative electrode sheet. Weigh 18 kg of hard carbon material, conductive carbon black, PTFE and carbon fiber in a ratio of 96.5:1.0:2:0.5, and prepare it using the same process as the positive electrode sheet.

[0138] Step 3: Assemble the battery cell. The electrode sheet is transferred to the winding process, and the positive and negative electrode sheet separators are rolled into a roll core using a PP separator. Then the battery is placed in a case, the electrode ears are welded, and the cover plate is welded. The battery is then placed in a vacuum environment until the pressure drops to 13 Pa, and then baked within 48 hours.

[0139] Step 4: Inject the first type of electrolyte into the battery cell. The first type of electrolyte is a mixture of DOL, FEC, HDI, EC, and DEC in a ratio of 20:15:15:15:15, containing 0.5 mol / L NaPF6 and 0.5% by mass of initiator AIBN. After injecting the electrolyte at 45°C, vacuum seal the battery cell and leave it for 48 hours.

[0140] Step 5: Heating treatment: Use a restraint fixture to fix the battery cell and heat it at 75°C for 3 hours.

[0141] Step six, inject the second type of electrolyte into the battery cell. After heating, cut the battery cell mouth and inject the second type of electrolyte, which is a mixture of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1-hexyl-3-methylimidazolium hexafluorophosphate, and EC in a weight ratio of 3:6:1, and add 0.5 mol / L NaPF6. Then evacuate and seal the battery cell and leave it at 45°C for 48 hours to complete the battery formation process. After formation, laser weld the aluminum plate with the injection hole and divide the volume, and finally obtain a sodium ion battery that can inhibit gas production.

[0142] Comparative Example 2

[0143] The difference from Example 5 is that the first type of electrolyte is not injected into the battery, and the second type of electrolyte is directly added.

[0144] Step 1: Prepare the positive electrode sheet. According to the weight ratio of 96:1.5:2.0:0.5, put the ternary sodium positive electrode material, conductive carbon black, PVDF and carbon fiber into a stirring kettle and mix them. After stirring for 30 minutes, add NMP until the solid content reaches 60%, and continue to stir at high speed for 3 hours. The obtained slurry is 190mg / m 2 The surface density is evenly coated on a 12um thick aluminum foil, and then rolled, slit and die-cut to form the positive electrode sheet.

[0145] Step 2: Prepare the negative electrode sheet. Weigh 18 kg of hard carbon material, conductive carbon black, PTFE and carbon fiber in a ratio of 96.5:1.0:2:0.5, and prepare it using the same process as the positive electrode sheet.

[0146] Step 3: Assemble the battery cell. Alternately stack 35 positive electrode sheets and 36 negative electrode sheets with PP separators to form a battery cell. Then weld the tabs, encapsulate the aluminum-plastic film, and place the battery in a vacuum environment until the pressure drops to 13 Pa, and then bake it within 48 hours.

[0147] Step 4: Inject the second type of electrolyte into the battery cell. The second type of electrolyte is a mixture of FEC, 2-fluoro-1,3-dimethylimidazolium chloride hexafluorophosphate, and EC in a ratio of 3:6:1, containing 0.5 mol / L NaPF6. At 45°C, after injecting the electrolyte, the battery cell is vacuum sealed and left for 48 hours to complete the battery formation process. After formation, it is left at room temperature for 24 hours, and the second sealing and capacity separation process is performed to finally obtain a sodium ion battery that can inhibit gas production.

[0148] Battery performance comparison test

[0149] The test method for the battery's cycling performance is: first, the battery is charged at a constant current of 1C (10A) until the voltage reaches 3.9V, then switched to a constant voltage charge of 3.9V until the charging current drops to 0.5A, at which point a charging cycle is completed. After charging, the battery is left for 30 minutes, then discharged at a constant current of 1C (10A) to 1.5V, marking the end of a cycle. This process will continue until the battery's discharge capacity drops to 80% of its initial capacity, at which point the test is terminated.

[0150] The battery thickness change rate test is carried out according to the following steps: the battery is first charged to 3.9V at a constant current of 1C (10A), and then switched to a constant voltage charge of 3.9V until the current drops to 0.5A, and the initial thickness of the battery is recorded in this state. After that, the battery is placed in an environment of 55°C for 45 days. After the battery surface is completely flat, its thickness is measured and recorded again. By comparing the initial and final thickness values, the increase rate of the battery thickness is calculated. This test is designed to evaluate the volume expansion of the battery during long-term use. The test results are shown in Table 2.

[0151] Table 2 Electrical performance test results

[0152] Capacity retention after 500 cycles % Thickness increase rate % Example 1 96.6 10.4 Example 2 96.1 13.2 Example 3 95.6 12.8 Comparative Example 1 79.7 28.1

[0153] It can be seen that in this patent, by adopting an electrolyte additive that can combine with the carbon on the surface of the electrode material and self-crosslink, a film layer that inhibits gas production is formed on the surface of the electrode, thereby improving the stability of battery operation.

Claims

1. A sodium ion battery sodium manganese ferrite positive electrode material, characterized in that: The chemical formula of the positive electrode material is Na a Mn b Fe c X d O 2-β , among which 0.6≤a≤0.9, 0.45≤b≤0.85, 0.25≤c≤0.55, 0≤d≤0.15, 0≤β ≤1, X is at least one element selected from Ca, Zn, Li, Mg, Zr, Ti, B, Nb, W, V, Si, Sr, Mo, Y and Al.

2. A sodium ion battery sodium manganese ferrite positive electrode material according to claim 1, characterized in that: The positive electrode material satisfies at least one of the following conditions: (1)0.75≤a≤0.85; (2)0.45≤b≤0.65; (3)0.25≤c≤0.45; (4)0≤d≤0.13。 3. The method for preparing the sodium ferromanganese positive electrode material for sodium ion battery according to claim 1, characterized in that: The following steps are involved: Step 1: primary crushing: crushing the precursor material obtained by sintering with an experimental airflow crusher; Step 2, secondary mixing, weighing the crushed precursor material, sodium source and additive according to the metal molar ratio of a:b:c:d, and mixing them using a test type high-efficiency mixer; Step 3: secondary sintering: placing the mixed materials in a muffle furnace for sintering in an air atmosphere to obtain a secondary sintered product; Step 4: secondary crushing: crush the secondary sintered material with an experimental airflow crusher to obtain NMFX material; Step 5: Screen and demagnetize the secondary crushed material to obtain sodium ferromanganate positive electrode material.

4. The method for preparing the sodium ferromanganese positive electrode material for sodium ion battery according to claim 3, characterized in that: The chemical formula of the precursor is Na a Mn b Fe c Li d O2, wherein 0.75≤a≤0.85, 0.45≤b≤0.5, 0.4≤c≤0.45, 0.05≤d≤0.13; the lithium source of the precursor is selected from at least one of lithium carbonate and lithium hydroxide monohydrate.

5. The method for preparing the sodium ferromanganese positive electrode material for sodium ion battery according to claim 4, characterized in that: The tap density of the precursor satisfies TD≥2.3g / cm 3 , the particle size distribution satisfies Span (D90-D10 / D50) ≥ 1.3, and the specific surface area satisfies BET ≥ 0.9 m2 / g.

6. The method for preparing the sodium ferromanganate positive electrode material for sodium ion battery according to claim 5, characterized in that: The preparation method of the precursor comprises the following steps: step a, a mixing step, weighing a manganese source and an iron source according to a metal molar ratio of α:(1-α), mixing the materials using a planetary ball mill to obtain a manganese-iron mixture, wherein 0.45≤α≤0.85; step b, a sintering step, subjecting the mixed manganese-iron mixture to a high-temperature solid-phase reaction to obtain a sodium ferromanganate positive electrode material precursor.

7. The method for preparing a sodium ferromanganese positive electrode material for a sodium ion battery according to claim 3, characterized in that: The grinding air pressure of the air flow mill described in step 1 is 0.4-0.8MPa, the classification frequency is 25-45Hz, the induced draft frequency is 15-35Hz, and the particle size of the material after grinding is D10=2.5±0.5μm, D50=7.0±0.5μm, and D90=12.5±0.5μm; The low speed of the mixer in step 2 is 200-500rpm / min, the mixing time is 2-10min, the high speed is 700-1000rpm / min, the mixing time is 10-50min; the unloading speed is 200-500rpm / min, and the unloading time is 30-60s; The secondary sintering time in step 3 is 10-25h, and the sintering temperature is 800-1000°C; The grinding air pressure of the air flow mill described in step 4 is 0.4-0.8MPa, the classification frequency is 25-45Hz, the induced draft frequency is 15-35Hz, and the particle size of the material after grinding is D10=2.5±0.5μm, D50=5.5±0.5μm, and D90=10±0.5μm.

8. The method for preparing sodium ferromanganate, a positive electrode precursor for sodium ion batteries according to claim 3, characterized in that: The manganese source described in step one is selected from at least one of manganese oxide, manganese carbonate and manganese hydroxide; the iron source is selected from at least one of iron oxide and ferrous hydroxide; the sodium source is selected from at least one of sodium carbonate and sodium bicarbonate; the main disk speed of the planetary ball mill described in step one is 50-200rpm / min, and the mixing time is 0.5-2h; the high-temperature solid-phase reaction temperature described in step two is 550-950℃, the sintering time is 5-20h, and the sintering atmosphere is air atmosphere.

9. Application of the sodium ferromanganate positive electrode material for sodium ion batteries according to claim 1 in sodium ion batteries, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, and a first electrolyte and a second electrolyte; the surfaces of the positive electrode sheet and the negative electrode sheet contain a carbon-based conductive agent, and the carbon-based conductive agent is selected from one or a mixture of hard carbon, carbon black, PVDF, PTFE, and carbon fiber; The first electrolyte includes: a cross-linking monomer, a diluent, a solute and an initiator, wherein the cross-linking monomer refers to a monomer having at least one functional group selected from the group consisting of a carboxyl group, a hydroxyl group, a ketone group, an ether group, an amino group, and a sulfonic group.

10. The use according to claim 9, characterized in that: The first electrolyte of the sodium ion battery comprises the following features: a weight ratio of the diluent is (60-90):(10-30), and the first electrolyte further contains 0.1-5 mol / L of solute and 0.1-3 wt% of initiator by mass, wherein the diluent is a carbonate diluent, the solute is NaPF6, and the initiator is AIBN; The cross-linking monomer is selected from the following group or a combination of several groups: Group 1: vinylene carbonate (VC) and acrylonitrile (AN); and the weight ratio range is 30-60:20-40; Group 2: polyethylene glycol diacrylate (PEGDA) and ethoxylated trimethylolpropane triacrylate (ETPTA); and The weight ratio range is 30-50:30-50; Group 3: 1,3-dioxolane (DOL), fluoroethylene carbonate (FEC), hexamethylene diisocyanate (HDI); and the weight ratio range is 10-30:10-25:10-25.